Daya Tarik Ekowisata Gunung Galunggung Sebagai Destinasi Wisata Alam - Inka Nur Farida; Asti Fauziah; Dimas Surya Lesmana; Ikhsan Maulana (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2026)
This study is motivated by the substantial natural, geological, and social potential of the Gunung Galunggung area, which has not yet been fully developed as a sustainable ecotourism destination. The site offers various attractions, including its scenic crater panorama, natural hot springs, iconic stairway routes, and the involvement of local communities that has the potential to enhance local welfare. This study employs a descriptive qualitative method, with data collection comprising field observations, interviews with visitors, and document analysis. The data were analyzed through processes of data reduction, data presentation, and conclusion drawing to describe the conditions of tourist attractions, supporting facilities, and socio-economic impacts. The findings indicate that Gunung Galunggung has strong natural and educational appeal, with reasonable accessibility, though several facilities still need improvement. Visitors perceive local hospitality as a positive aspect, while tourism activities contribute to the local economy. The main challenges include limited facilities, insufficient digital promotion, and low environmental awareness among some visitors. Overall, Gunung Galunggung has substantial potential to be developed as a sustainable ecotourism destination through improved infrastructure, environmental education, digital promotion, and active involvement of local communities.